IMPLEMENTASI LAYANAN KOMPONEN KESEHATAN PADA PROGRAM KELUARGA HARAPAN (PKH) : (Studi Kasus di Kecamatan Slogohimo Kabupaten Wonogiri) - Budhi (Jurnal Ilmu Kesehatan Masyarakat Berkala (JIKeMB), 2023)
The rapid population growth in Indonesia necessitates an increase in societal welfare, including education, health, and economic conditions. One of the government's efforts to enhance citizen welfare is the Family Hope Program (PKH), which provides conditional social assistance to impoverished families. This research focuses on the implementation of the health component of PKH in Slogohimo District, Wonogiri Regency, examining its effectiveness and impact on local welfare. Data from the Central Statistics Agency indicates rising poverty levels and significant health challenges in the area, including high rates of maternal mortality and child stunting. This study aims to describe the implementation process of PKH's health services, its effects on community welfare, and the factors influencing its success or hindrance. Findings reveal that the PKH health component has yet to be fully effective due to issues such as delayed fund disbursement and inaccurate targeting of beneficiaries. Despite these challenges, PKH has positively impacted health behaviors, reduced household expenditure, and contributed to modest income increases. However, improvements are needed in the accuracy of beneficiary data and timely fund distribution. Recommendations include stricter adherence to PKH guidelines, enhanced monitoring and evaluation, and ongoing data validation to ensure the program reaches the most vulnerable populations